Synthesis of 3-Sulfenylindoles from Indoles and Various Sulfenylation Agents through Aerobic Oxidative C–S Bond Coupling - Xu, Chaorong; Yi, Shanli; Li, Meichao; Hu, Xinquan; Sun, Nan; Jin, Liqun; Hu, Baoxiang; Shen, Zhenlu (Synlett, 2018)
A novel aerobic catalytic oxidation system for the sulfenylation of indoles with a variety of sulfenylation agents through oxidative C–S bond coupling has been successfully developed. The reactions were performed with potassium iodide as the catalyst, sodium nitrite as the co-catalyst, and molecular oxygen as the terminal oxidant in the presence of acetic acid. Under the optimal reaction conditions, a number of indoles could be sulfenylated with Bunte salts, thiols, or disulfides to generate 3-sulfenylindoles in good yields. This protocol provided an efficient and environmentally benign strategy for the synthesis of 3-sulfenylindoles.
Keywords: indoles; sulfenylation; C–S bond coupling; catalytic oxidation; regioselectivity